Potential Analysis of High-g Shock Experiment Technology for Heavy Specimens Based on Air Cannon - Zhengyong Duan; Tianhong Luo; Dayong Tang (Shock and Vibration)
According to the technical requirements of harsh shock environment test, this paper presents the study on the pneumatic vertical test technology with large load and high-g value. The inspiration of this paper comes from the fact that a compressed air cannon can produce instantaneous and powerful air jets that can be used to drive the tested object to achieve a high initial collision velocity. Then, the principle of shock test technology based on an air cannon and an impact cylinder was put forward, and the idea gas mechanics model was established to theoretically analyze the laws that how the parameters of the air cannon and cylinder influence the initial impact velocities. The test system was built, and the test research was carried out. When the air cannon pressure is 0.5 MPa and 0.65 MPa, respectively, under no-load, the impact acceleration measured is 1990 g (pulse width, 1.26 ms) (1g = 9.8 m/s2) and 4429 g (pulse width, 1.20 ms). It preliminarily validated the effectiveness and feasibility.